Bouts of fever - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
After Yemen and Saudi Arabia, now it is the turn of Kenya to be hit by cases of Rift Valley fever. This virus is carried by mosquitoes and attacks animals, though it can also attack humans. Sudan has closed its borders with Kenya to limit the spread...